WHAT SUSTAINS THE SUSTAINABLE? AN EMPIRICAL ANALYSIS OF ECONOMIC, SOCIAL AND ENVIRONMENTAL FACTORS IN OECD COUNTRIES (Contemporary Journal of Social Science Review, 2025)
This study investigates the determinants of economic, social and environmental sustainability in OECD countries using panel data from 38 member nations over the period 2000–2023. The study has analyzed economic sustainability through GDP growth, social sustainability via secondary school enrollment and environmental sustainability through CO₂ emissions using a robust methodology of Cross-Sectionally Augmented ARDL (CS-ARDL) model. The findings reveal that gross fixed capital formation, labor force participation, trade openness, financial development, and foreign direct investment significantly enhance economic sustainability while population density and CO₂ emissions negatively impact it. Social sustainability is positively influenced by GDP growth, urbanization, and population density whereas inflation and unemployment exert negative effects. Environmental sustainability increases with GDP, foreign direct investment, urbanization and population growth though the squared GDP term reflects a potential turning point in the Environmental Kuznets Curve. Based on these results, the study proposes targeted policy recommendations for promoting sustainability. The study contributes to the empirical literature on sustainability by providing comprehensive, policy-relevant insights grounded in the OECD context.